Apnoeic oxygenation during paediatric tracheal intubation: a study protocol for a single-centre, cluster randomised clinical trial (ApOx-Pedi-Trial) - Uzun, Davut D.; Zimmermann, Benjamin P.; Knöller, Sebastian; Kirchner, Marietta; Mohr, Stefan; Weigand, Markus A.; Živković, Aleksandar; Schmitt, Felix (BMJ open, 2025)
Introduction Adverse events during paediatric anaesthesia are common, with hypoxaemia during the induction period being a leading cause, as infants and children are particularly vulnerable to hypoxaemia during periods of apnoea. The administration of supplementary oxygen, referred to as apnoeic oxygenation, has been shown to prolong safe apnoea times and increase first-pass intubation success rates. Despite these benefits, apnoeic oxygenation is not routinely used in paediatric anaesthesia. Low-flow apnoeic oxygenation, delivered via a standard nasal cannula, is a simple approach to provide supplementary oxygen during paediatric airway management without requiring additional equipment. However, its efficacy in airway management during elective surgeries has not been adequately studied. - Methods and analysis The ApOx-Pedi-Trial is a single-centre, cluster randomised, controlled clinical trial comparing the use of low-flow apnoeic oxygenation during the induction of general anaesthesia in infants and children up to 6 years of age undergoing elective surgery at the Department of Pediatric Surgery at Heidelberg University Hospital to standard of care (no apnoeic oxygenation). Randomisation is conducted using a weekly cluster randomisation method, where all patients presenting for surgery in a given week either receive apnoeic oxygenation or standard of care during the induction of general anaesthesia, based on the week’s group allocation.The study population will consist of two independent, age-stratified cohorts (<24 months and >24 months to 6 years), each including 100 patients. Statistical analysis of study endpoints will be conducted separately for each cohort to allow for age-specific assessment of outcomes.The primary objective of this trial is to evaluate whether apnoeic oxygenation can prevent a decrease in transcutaneous haemoglobin saturation (SpO₂) during the induction of general anaesthesia in infants and children. The primary outcome measure will be the lowest recorded SpO₂ value throughout the apnoeic period. - Ethics and dissemination The ApOx-Pedi-Trial received permission from the local ethics committee (Ethics Committee of the medical faculty at Heidelberg University, Heidelberg, Germany) under the registration number S-074-2024. The study is following institutional Guidelines and the Declaration of Helsinki of 1975 in its most recent version. Trial results will be submitted to peer-reviewed journals and presented at national and international conferences. - Trial registration number The trial is prospectively registered on ClinicalTrials.gov with the number NCT06576596.
Gesehen am 14.10.2025